Trends in scientific production in telecommunications (1981–2023): a bibliometric study - Quezada Castro, Guillermo Alexander (2024)
Purpose: Telecommunications have evolved in response to technological advancements and regulatory changes established in law. There remains a research gap concerning universal access to communication rights, which can be addressed through a bibliometric analysis of the scientific literature. This study aimed to identify trends in telecommunications research. Accordingly, it analyzed annual scientific output, determined the most representative journals, examined prevalent keywords, highlighted the most productive authors, and identified key articles in the field. Methods: Scientific production was analyzed using the Scopus database. Documents published between 1981 and 2023 in English were included, while those not relevant to the study topic were excluded. A total of 237 documents were analyzed using the Biblioshiny interface and Microsoft Excel. Results: Annual scientific output peaked in 2021, with an annual growth of 2.91%. The most representative journal was Telecommunications Policy. The consolidated keywords were “communication rights,” “public service media,” “media policy,” “regulation,” and “telecommunications.” The most productive authors were Amy Sanders and Pradip Thomas. The most cited article addressed the institutional foundations of telecommunications regulation. Conclusion: There was evidence of growing scientific production in telecommunications, published in high-impact journals with an interdisciplinary approach. The main topics related to telecommunications were communication rights, regulation, and internet governance. Despite the presence of prolific authors, a need for greater collaboration in the formation of international research networks was identified.